Keeping the family together: Sustainability and modularity in community source development. Issue 1 (March 2020) - Liu, Manlu; Hansen, Sean; Tu, Qiang
Abstract: Community-based open source software development ("community source") is an approach that leverages selected strengths of both the commercial and open source software development. The community source approach centers on the formation of formal communities among institutions based on principles of shared investment and collaborative action to achieve mutually-desired goals. However, as with ordinary open source projects, sustainability can be a significant challenge as development communities grow and evolve. In the present study, we explore the opportunities and challenges to the community source approach through a longitudinal study of a real world community source project, Kuali. Specifically, we apply the principles of modular systems design and design structure matrix modeling to achieve an in-depth understanding of the mechanisms for sustainability in collaborative systems development. In so doing, we introduce a quantitative measure of architectural modularity within an inter-organizational structure. A number of implications are presented for the conduct of research on community source development as well as the design of collaborative communities more broadly defined. Highlights: Community-source development enjoys benefits of commercial and open source models. Community growth presents an array of challenges to community-source efforts. DSM modeling enables graphical assessment and analysis of collaborative modularity. Architectural modularity can inform design of inter-organizational collaborations. Modular organization design enables balance of community growth and sustainability.